Evaluation Indicators of Tourism Development In The City of Kashan (تحقیقات کاربردی علوم جغرافیایی)
Today, tourism is the high level of development to the economies of most countries in the world have provided, as the basic unit of economic development is considered. In the meantime, the attributes or characteristics of tourism resources to be able to perform activities of tourism, destination guides. On the other hand Kashan city with a long history and its historical Each year, has attracted many domestic and foreign tourists and tourism at the national level to shine as a city. The purpose of this study was to evaluate indicators of Kashan tourism development strategy based on four criteria: comfort, competitiveness, information technology and communications and tourism management. This research method in terms of purpose and terms of method, is descriptive. The method relies on the harvest field data collection using a questionnaire that has been obtained through Cochran Formula 382.The study group this study included groups of tourists, which is in the research questionnaire, each from each group was given the status of tourism development indicators of in Kashan be determined. After the above steps to classify data using SPSS the software and one-sample t test through the conclusion reached. The city of Kashan in terms of all indicators of tourism development (with the exception of information and communication technologies), as was proper, and in general indicators of tourism development Kashan is higher than the theoretical mean. The relevant authorities in relation to information technology and communication possibilities in the tourist sites should offer new strategies that can obtain the consent of tourists and the proposed strategies were presented.